2010
DOI: 10.1111/j.1439-0329.2010.00672.x
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution of Raffaelea quercivora hyphae in transverse sections of seedlings of two Japanese oak species

Abstract: To compare the distributions of Raffaelea quercivora hyphae within seedlings of a susceptible species, Quercus crispula, and a resistant species, Q. glauca, we examined water conductance at transverse sections. Raffaelea quercivora was inoculated into the stems of seedlings in July (summer) and October (autumn) and observed by light and fluorescence microscopy at 1 and 2 weeks after inoculation. The hyphal distribution patterns expressed as the I d index differed between the species at each occasion. The hypha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(24 citation statements)
references
References 13 publications
3
20
0
1
Order By: Relevance
“…In the present study, inoculations with the fungus caused larger non-conductive areas compared with the controls in Q. coccinea and Q. palustris. In fact, the spatial distribution of R. quercivora hyphae was shown to coincide with non-conductive sapwood (Takahashi et al 2010;Torii et al 2011). However, little is known about the death mechanism of non-native oak species by inoculations of R. quercivora.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the present study, inoculations with the fungus caused larger non-conductive areas compared with the controls in Q. coccinea and Q. palustris. In fact, the spatial distribution of R. quercivora hyphae was shown to coincide with non-conductive sapwood (Takahashi et al 2010;Torii et al 2011). However, little is known about the death mechanism of non-native oak species by inoculations of R. quercivora.…”
Section: Discussionmentioning
confidence: 99%
“…Ito (Ito et al 1998;Kubono and Ito 2002;Seo et al 2012), which is transmitted within mycangia of the ambrosia beetle Platypus quercivorus Murayama (Coleoptera: Platypodidae; Kinuura 2002;Kinuura and Kobayashi 2006). In fact, microscopic observation of transverse and longitudinal sections suggests that most hyphae of the fungus under both artificial and natural conditions were detected in non-conductive sapwood, irrespective of the time elapsed since the inoculation or infection (Kuroda 2001;Takahashi et al 2010;Murata et al 2011;Torii et al 2011). Although plants have various defence mechanisms against microbial pathogens and herbivores (Doehlemann and Hemetsberger 2013;Moles et al 2013), in this disease, the formation of non-conductive sapwood was suggested to be a defence response against fungal spread (Kuroda and Yamada 1996;Yamagishi et al 2013a,b).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In experiment 3, the sapwood discoloration widths of logs were sig nificantly larger than those of standing trees in some comparisons. In addition, the mortality of Q. crispula and Q. ser rata by the artificial inoculation of R. quercivora is influenced by the phenology of host trees (25,35,37), which tends to depend on host physiology. In addition, the mortality of Q. crispula and Q. ser rata by the artificial inoculation of R. quercivora is influenced by the phenology of host trees (25,35,37), which tends to depend on host physiology.…”
Section: Cont G37 Nr24 Rem10mentioning
confidence: 99%